SYMBOLIC COMMUNICATION IN THE BETTULAK RITUAL: HARMONY BETWEEN LOCAL BELIEFS AND EPIDEMIC PREVENTION STRATEGIES IN LENDANG ARA VILLAGE - Amri Malik Aziz Rahman; Faizah; Athik Hidayatul Ummah; Reza Perwira; Tubagus Dynar Erlandy (Penamas, 2025)
The Bettulak ritual is a hereditary tradition of the Lendang Ara community in Central Lombok, rich in symbolic values and local wisdom. After being dormant for nearly five decades, the tradition was revitalized in 2023 as a response to the threat of disease outbreaks and as an effort to strengthen cultural identity. This study aims to reveal the symbolic meanings, revitalization processes, and cultural negotiations involved in the performance of Bettulak in the modern era. Using a qualitative approach with field research methods, data were collected through participant observation, in-depth interviews, and documentation. The analysis draws on Mead and Blumer’s theory of symbolic communication as well as Geertz and Carey’s cultural communication approaches. The findings indicate that Bettulak functions as a medium of symbolic communication that strengthens social cohesion, reproduces religious and traditional values, and serves as a space for negotiation between modernity and tradition. The ritual’s revitalization not only restores cultural practices but also shapes a new narrative about the sustainability of the Lendang Ara community’s collective identity amid the currents of globalization. These findings underscore the importance of preserving traditions as an adaptive cultural communication strategy relevant to contemporary contexts